Postoperative MR Defecography following Failed STARR Procedure for Obstructive Defecation Syndrome: A Three-Centre Experience - Vittorio Piloni; Marco Possanzini; Mattia Bergamasco; Gianluca Santi (Gastroenterology Research and Practice)
Aim. To describe the abnormalities at MR imaging and related complaints in patients with poor outcome after STARR procedure. Materials and Methods. The medical records of 21 symptomatic patients from centre 1, 31 patients from centre 2, and 63 patients from centre 3 were reviewed with regard to findings at MR defecography and related symptoms. Results. Regardless of the centre, most relevant imaging features and related complaints were (a) impaired emptying (82.11%), related complaint ODS; (b) persistent rectocele >2 cm and intussusception (39.3%), split evacuation and digitation; (c) pelvic organ descent on straining (39.8%), prolapse sensation; (d) small neorectum and loss of contrast (32.5%), urgency and incontinence; (e) anastomotic stricture and granuloma (28.4%), pain; and (f) nonrelaxing puborectalis muscle (19.5%), tenesmus. Less frequent findings included rectal pocket formation (5.6%) and rectovaginal sinus tract (1.6%). Patients were referred to MR imaging with an average time interval of 5 ± 2, 4 ± 1, and 2 ± 1 years in the three centres, respectively, and only rarely by the same surgeon who performed the operation: 1/21 (4.8%) in centre 1, 3/39 (7.7%) in centre 2, and 9/63 (14.3%) in centre 3. Conclusion. Most surgeons involved in STARR operation with subsequent poor outcome do not rely on MR imaging.